Experimental and numerical investigation on phase change material filled reinforced cement concrete roof slab for mitigating the heat transfer. Issue 2 (15th June 2022) - Haridass, Karthick; N., Nallusamy; Rajkumar, S
ABSTRACT: In this paper, a phase change material (PCM) filled rooftop is proposed to reduce heat transfer from the roof. Experiments are conducted to compare the thermal characteristics of residential buildings with bare reinforced cement concrete roof (RCC) top without PCM and PCM filled RCC rooftop in the summer season. Aluminum panels containing macro encapsulated PCM, which occupies around 66% of the total roof slab area, are employed in one of the building rooftops. They store the heat energy in the form of latent heat and thus reduce the heat transfer into the building. In the RCC roof slab of thickness 0.152 m, 0.051 m is allotted for storing PCM and the remaining 0.101 m ensures adequate strength of the roof slab. The comparisons of thermal behavior between the buildings of bare and PCM integrated RCC roofs reveal that the PCM integrated roof reduced the heat transfer into the building vis-à-vis bare roof building. The PCM integrated roof diminished the heat flux to a maximum of 53% compared to the non-PCM roof on the day when the maximum temperature was recorded (18 May 2021) during the experimental periods. In PCM filled roof, an average reduction of 2°C in the room temperature is achieved as compared to that of a non-PCM filled roof.